2016
DOI: 10.1128/jcm.00743-16
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Significance of Staphylococcus epidermidis in Health Care-Associated Infections, from Contaminant to Clinically Relevant Pathogen: This Is a Wake-Up Call!

Abstract: ) describes a rapid single nucleotide polymorphism-based assay for distinguishing between S. epidermidis isolates from hospital and nonhospital sources, which represents an important contribution to the characterization and understanding of S. epidermidis health careassociated infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 31 publications
(33 reference statements)
1
45
0
Order By: Relevance
“…Although commensal S. epidermidis isolates display high rates of resistance to antibiotics of clinical relevance (Morgenstern et al, 2016a ), their default status as commensal bacteria renders this phenomenon largely irrelevant for the healthy human host. However, with the advent of implanted medical devices such as prosthetic joints and fracture fixation devices, S. epidermidis has emerged as an important opportunistic pathogen (Otto, 2009 ; Widerstrom, 2016 ). In fact, the implanted medical device may actually facilitate infection since any S. epidermidis inadvertently introduced into the surgical site are capable of rapidly adhering to, and accumulating upon, the surface of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Although commensal S. epidermidis isolates display high rates of resistance to antibiotics of clinical relevance (Morgenstern et al, 2016a ), their default status as commensal bacteria renders this phenomenon largely irrelevant for the healthy human host. However, with the advent of implanted medical devices such as prosthetic joints and fracture fixation devices, S. epidermidis has emerged as an important opportunistic pathogen (Otto, 2009 ; Widerstrom, 2016 ). In fact, the implanted medical device may actually facilitate infection since any S. epidermidis inadvertently introduced into the surgical site are capable of rapidly adhering to, and accumulating upon, the surface of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulase-negative staphylococcus (CoNS) is a part of the commensal bacterial microflora of healthy people. However, with the development of interventional therapy and the increasing number of immunocompromised patients, these bacteria are becoming the most important causes of nosocomial infections [ 1 , 2 ]. CoNS bloodstream infections have been estimated in as many as 250,000 cases annually in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, we found that biofilm formation was frequent among our strains isolated from catheters and blood cultures. This observation is well associated with advantages provided by biofilm as a life mode to conquer hospital environment (25). Furthermore, important observation to note is that a considerable number of catheter isolates were unable to form biofilm.…”
Section: Discussionmentioning
confidence: 93%